The Govemment of OKI Jakarta had built the new TPI (Tempat Pelelangan likan) in Muara Angke to replace the function of the old TPI. This new TPI have equipped an improving facility and service of quality cause of service and managerial problems of the old TPI. These problems are hygiene and sanitary, capacity of auction sale area and security. Success of TPI management service influenced of user subjective perception on it perceived quality. Therefore, measurement of satisfaction of the auction - Popong Nurhayati; Iis Diatin; Teguh Suryanto (Buletin Ekonomi Perikanan, 2007)
The Govemment of OKI Jakarta had built the new TPI (Tempat Pelelangan likan) in Muara Angke to replace the function of the old TPI. This new TPI have equipped an improving facility and service of quality cause of service and managerial problems of the old TPI. These problems are hygiene and sanitary, capacity of auction sale area and security. Success of TPI management service influenced of user subjective perception on it perceived quality. Therefore, measurement of satisfaction of the auction sale participants toward the care service attributes of TPI Muara Angke is required. This research is aimed to identify level of satisfaction of auction sale participants toward the service attributes of TPI, how is the management orientation of accurate service attributes in TPI Muara Angke, how is the quality of care service perceived by auction sale participants in TPI Muara Angke, and how is suitability of perception of auction sale participants toward the perceived quality in TPI Muara Angke. Result of the research showed that generally, auction sale participant feel satisfied with the performance care of TPI Muara Angke. Its shown in value of customer satisfaction index 0,73763 that caused of service quality improvement the new TPI Muara Angke which has more completely facility service. According auction sale participants, care service of new TPI Muara Angke is better than the old TPI Muara Angke. The auction sale participants between the new TPI Muara Angke and the old TPI Muara Angke gave different assessment about quality of each service' attributes. It means there's no suitability perceived quality between the new TPI Muara Angke and the old TPI Muara Angke. The auction sale participants have different perception about quality of service attributes both TPI.